2022
DOI: 10.1021/acsomega.2c04102
|View full text |Cite
|
Sign up to set email alerts
|

Investigations to Explore Molecular Interactions and Sweetness Response of Polyhydroxy Compounds with Amino Acids in Aqueous Systems

Abstract: In conjunction with the development of people's living standards, the modern world demands good-quality food such as sweets, candies, chocolates, diet drinks, beverages, and so on, but because of obesity and other health issues people concentrate more on sugar-free or low-calorie products. Polyols are such a kind of food with desirable qualities, and they play a role in controlling the blood glucose level in diabetic patients. The density (ρ) and sound speed (u) of sugar alcohol in water and in (0.02, 0.04, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Knowledge acquired from limiting the apparent molar volume (Φ v ° ) is a very important parameter to analyze the interactions happening in solution. Evaluation of limiting apparent molar volumes (Φ v 0 ) was carried out using eq obtained from the plots of Φ v versus m by a least-squares treatment. normalΦ normalv = normalΦ normalv 0 + S normalv * m where Φ v 0 is the limiting apparent molar volume (m 3 ·mol –1 ) at infinite dilution and S V * (m 3 ·mol –2 ·kg) denotes the experimental slope, which is considered as a pairwise volumetric virial coefficient. The physical significance of S V * indicates the solute–solute interactions among the amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge acquired from limiting the apparent molar volume (Φ v ° ) is a very important parameter to analyze the interactions happening in solution. Evaluation of limiting apparent molar volumes (Φ v 0 ) was carried out using eq obtained from the plots of Φ v versus m by a least-squares treatment. normalΦ normalv = normalΦ normalv 0 + S normalv * m where Φ v 0 is the limiting apparent molar volume (m 3 ·mol –1 ) at infinite dilution and S V * (m 3 ·mol –2 ·kg) denotes the experimental slope, which is considered as a pairwise volumetric virial coefficient. The physical significance of S V * indicates the solute–solute interactions among the amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…The above-mentioned explanation suggested that the molecular interaction behavior of L-Met with ionic liquid (BTMAC and BTEAC) dominates over L-Met with L-Met in all cases of solutions. 33,36 The resultant volume contractions that occurred in the systems echo the hydrophobic interactions in the amino acids by the caging effect of the water molecule or hydrophobic hydration. 37 Values from previous literature show that similar types of links have been identified for homologous series of amino acids in electrolyte solutions in an aqueous medium.…”
Section: S Mmentioning
confidence: 99%
“…Among the various pollutants, synthetic dyes such as rhodamine B, 279–281 Sudan red III, 282–285 methyl red, 286–288 methyl violet, 289–293 malachite green, 294,295 acid black dye, 296–299 Congo red, 300 and methyl orange 301–303 are common. Feng et al created CsPb(Br 1− x Cl x ) 3 -Au nanoheterojunction materials, 271 which were used to decompose Sudan red III pollutants, and the results showed that after 6 hours of visible light exposure, the heterostructures had degraded 71% of Sudan dye.…”
Section: Applications Of All-inorganic Halide Perovskitesmentioning
confidence: 99%
“…Among the various pollutants, synthetic dyes such as rhodamine B, [279][280][281] Sudan red III, [282][283][284][285] methyl red, [286][287][288] methyl violet, [289][290][291][292][293] malachite green, 294,295 acid black dye, [296][297][298][299] Congo red, 300 and methyl orange [301][302][303] Besides dyes, the abuse of broad-spectrum antibiotics (ciprooxacin, 305-307 noroxacin, 308-311 2-mercaptobenzothiazole, 312 and tetracycline hydrochloride [313][314][315] ) causes harm to ecosystems and poses a threat to human health. Using allinorganic lead halide perovskites, antibiotics can be successfully removed from water sources.…”
Section: Contaminant Degradationmentioning
confidence: 99%
“…The hexitol family includes the sugar alcohol known as D -mannitol. Due to their low-calorie content, minimal impact on blood sugar levels, decreased absorption by the intestines, reduced risk of dental caries, and delightful sweetness, sugar alcohols are used as artificial sweeteners in food, candy, pharmaceutical, and confectionary products all over the world. It replaces regular for diabetes and obese people as no requirement is made by them for metabolism .…”
Section: Introductionmentioning
confidence: 99%